COMMUNICATIVE LANGUAGE TEACHING IS ONE OF SIGNIFICANT APPROACHES IN DEVELOPING LANGUAGE SKILLS - Jumayeva Shahlo Shokirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The ever-growing need for good communication skills in English has created a huge demand for English teaching around the world. Millions of people today want to improve their command of English or to ensure that their children achieve a good command of English. There are a number of teaching methods in the literature and articles on new pedagogical technologies. These methods are presented as innovative methods. Here are some of the methods that can be used in foreign and even native language lessons.